The Development of Myelin in the Brain of the Juvenile Rat. (July 2014) - Downes, Noel; Mullins, Pamela
The development process of myelination varies between region and species. Fully myelinated fibers are required if mammalian neural circuits are to function normally. Histology samples at staggered time points throughout the study were examined at days 4, 5, 7, 8, 10, 14, 17, 24, 37, and 44. We suggest that the development of myelin in the juvenile rodent brain can be conveniently separated into 3 phases. Evaluation of myelin basic protein–stained sections of the areas of brain that contain the elements of the developing limbic system over the sensitive period from postnatal day (PND) 14 to 34 may provide an insight into possible toxicity that may lead to cognition and learning issues in adults. We will hope to develop this notion further in the future. The precise chronology of the development of the blood–brain barrier in rats has yet to be established; thus, there is potential for significant exposure of the juvenile brain to chemicals that do not cross the blood–brain barrier in the adult. Thus, it is suggested that evaluation of myelin development should probably be extended to all new chemical entities intended for pediatric use, and not just those that are intended for central nervous system use.